Complementary and integrative healthcare communication in Chinese American patient / primary care visits: An observational discourse analysis - Evelyn Y. Ho; Genevieve Leung; Brady Lauer; Jane Jih; Leah Karliner (Elsevier, 2022)
Objective: Chinese-American patients use CIH at high rates but disclosure of CIH use to clinicians is low. Further, the content of CIH talk between patients and their clinicians is not well described. We aimed to characterize CIH talk between Chinese-American patients and their primary care clinicians. Methods: Discourse analysis of 70 audio-recordings of language concordant and discordant-interpreted visits. Results: Nearly half of all visits (48.6%) had some form of CIH communication. 'Simple CIH talk' focused on a single CIH topic resulting in a positive, neutral, or negative response by clinicians. 'CIH-furthering talk' was characterized by clinicians and patients addressing more than one CIH topic or including a combination of orientations to CIH by both clinicians and patients. CIH-furthering talk characterized by clinician humility could enhance rapport, cultural understanding, and open communication. CIH-furthering talk also led to miscommunication and retreat toward biomedicine. Conclusion: CIH communication occurred frequently during language concordant and discordant-interpreted visits with Chinese-American patients. Both patients and clinicians used CIH-furthering talk as a conversational resource for managing care. Innovation: This discourse analysis of visits between Chinese-American patients and their clinicians advances understanding of CIH communication beyond disclosure, illustrating the complexity of linguistic and cultural nuances that affect patient care.